Preliminary Study of White Matter Abnormalities and Associations With the Metabotropic Glutamate Receptor 5 to Distinguish Bipolar and Major Depressive Disorders - Siyan Fan; Ruth H. Asch; Margaret T. Davis; Nicole DellaGioia; Ryan Cool; Hilary P. Blumberg; Irina Esterlis (Chronic Stress, 2024)
Background Understanding distinct neurobiological mechanisms underlying bipolar disorder (BD) and major depressive disorder (MDD) is crucial for accurate diagnosis and the discovery of novel and more effective targeted treatments. Previous diffusion-weighted MRI studies have suggested some common frontotemporal corticolimbic system white matter (WM) abnormalities across the disorders. However, critical to the development of more precise diagnosis and treatment is identifying distinguishing abnormalities. Promising candidates include more prominent frontotemporal WM abnormalities observed in BD in the uncinate fasciculus (UF) that have been associated with frontal-amygdala functional dysconnectivity, and with suicide that is especially high in BD. Prior work also showed differentiation in metabotropic glutamate receptor 5 (mGlu5) abnormalities in BD versus MDD, which could be a mechanism affected in the frontotemporal system. However, associations between WM and mGlu5 have not been examined previously as a differentiator of BD. Using a multimodal neuroimaging approach, we examined WM integrity alterations in the disorders and their associations with mGluR5 levels. Methods Individuals with BD ( N  = 21), MDD ( N  = 10), and HC ( N  = 25) participated in structural and diffusion-weighted MRI scanning, and imaging with [ 18 F]FPEB PET for quantification of mGlu5 availability. Whole-brain analyses were used to assess corticolimbic WM matter fractional anisotropy (FA) across BD and MDD relative to HC; abnormalities were tested for associations with mGlu5 availability. Results FA corticolimbic reductions were observed in both disorders and altered UF WM integrity was observed only in BD. In BD, lower UF FA was associated with lower amygdala mGlu5 availability ( p  < .05). Conclusions These novel preliminary findings suggest important associations between lower UF FA and lower amygdala mGlu5 levels that could represent a disorder-specific neural mechanism in which mGluR5 is associated with the frontotemporal dysconnectivity of the disorder.